A sophisticated fracture classification system of the proximal femur trochanteric region (AO/OTA-31A) based on 3D-CT images - Chang, Shi-Min; Wang, Zhen-Hai; Tian, Ke-Wei; Sun, Gui-Xin; Wang, Xin; Rui, Yun-Feng (Frontiers in Surgery, 2022)
Objective Fracture classification evolves dynamically with new and enhanced imaging modalities. This paper aims to introduce a novel hypothesis of a sophisticated fracture classification system for the proximal femur trochanteric region (AO/OTA-31A) based on 3D-CT images and accommodate the clinical requirement of the worldwide outbreak of geriatric hip fractures with large amounts of surgical operations. Methods In the current practice of widely preoperative 3D-CT application and cephalomedullary nailing, we attempt to propose a new comprehensive classification system to describe the fracture characteristics in a more detailed and sophisticated architecture, and pay the most important concern to the parameters that contribute to fracture stability reconstruction in osteosynthesis. Results The new four-by-four comprehensive classification system, followed the structure of the AO/OTA system, incorporates many fracture characteristics as dividing indexes into multiple grade levels, such as fracture line direction, the number of fragments, the lesser trochanter fragment and its distal extension (>2 cm), the posterior coronal fragment and its anterior expansion (to the entry portal of head–neck implant at the lateral cortex), the lateral wall and anterior cortex fracture, and the anteromedial inferior corner comminution. From a panoramic perspective, there are four types and each type has four subtypes. A1 is simple two-part fractures (20%), A2 is characterized by lesser trochanter fragment and posterior coronal fractures (62.5%), A3 is reverse obliquity and transverse fractures with complete lateral wall broken (15.5%), and A4 is medial wall comminution which further lacks anteromedial cortex transmission of compression force (2%). For subtypes, A2.2 is with a banana-like posterior coronal fragment, A2.4 is with distal cortex extension >2 cm of the lesser trochanter and anterior expansion of the posterior coronal fragment(s) to the entry portal of head–neck implants, A3.4 is a primary pantrochanteric fracture, and A4.4 is a concomitant ipsilateral segmental fracture of the neck and trochanter region. Conclusion Classification represents diversity under consistency. The four-by-four sophisticated classification system delineates fracture characteristics in more detail. It is applicable in the time of rapid outbreak of trochanteric fractures in the older population, the large amounts of surgical operations, and incorporates various rare and/or more complicated subtypes which is unclassifiable before.